2017
DOI: 10.1016/j.diii.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Günther Tulip filter tilting during transfemoral placement

Abstract: Significant association of the pre-deployment angle with post-deployment GTF tilting was shown in both the experimental and clinical studies. The experimental study also showed that proximity of filter legs is relevant when pre-deployment angle is small. Addressing these factors may result in a lower incidence of filter tilting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In this study, for transfemoral access, the bent wire technique had a lower filter tilt ratio than did the original push or hydrophilic stiff wire techniques. The angle between the IVC and the iliac vein affects filter tilting at deployment [23][24][25]. The bentwire technique reduces the angle and allows the filter tip to be positioned in the center of the IVC lumen, as illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, for transfemoral access, the bent wire technique had a lower filter tilt ratio than did the original push or hydrophilic stiff wire techniques. The angle between the IVC and the iliac vein affects filter tilting at deployment [23][24][25]. The bentwire technique reduces the angle and allows the filter tip to be positioned in the center of the IVC lumen, as illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study also investigated IVC filter positional parameters, and demonstrated that net filter tilt (defined as the difference in angulation from placement to retrieval) is associated with filter retrieval outcome (8). In addition, studies have examined the hemodynamic effects of lateral tilt, effect of tilt on filtration, and deployment techniques to minimize tilt during filter placement (9)(10)(11). However, the direct association of outcomes and placement lateral tilt have not been previously well studied.…”
mentioning
confidence: 99%